FREE RADICALS AND INFLAMMATION IN RATS OF DIFFERENT AGE IN CASES OF SODIUM NITRITES AND TOBACCO SMOKE POISONING - Lykhatskyy, P. H.; Fira, L. S. (International Journal of Medicine and Medical Research, 2017)
Background. Due to the wide use of nitrate fertilizers in agriculture and their migration into groundwater and food, the spreading of nitrate poisoning has become epidemic. However, people in the process of life get into bad habits: smoking, alcohol, drugs abuse. All these factors affect health and can cause fatal outcome. In real life, people are often exposed to more toxic factors that lead to general poisoning of the body and damage of many organs. Objective. The research was aimed to study the activity of free radicals and inflammation in rats of different age in cases of sodium nitrite affection with underlying 45-day tobacco intoxication. Methods. The content of nitrite ion (NO2-) was evaluated by Gris reaction. The level of pro-inflammatory (interleukin 6 (IL-6) and anti-inflammatory (interleukin 4 (IL-4) cytokines was determined in serum by ELISA method using test kits. Results. It was proved that in rats of different age affected by sodium nitrite with underlying 45-day tobacco smoke intoxication, the content of nitrite ion in serum, liver, lungs and myocardium is increased. After poisoning the animals with the studied toxicants, inflammation was activated in the body that was evidenced by the increased pro-inflammatory cytokine IL-6 and decreased inflammatory cytokine IL-4 in serum. Conclusions. The nitrite ion content in organs was the most significant and inflammation was manifested in the immature rats. In these animals the content of anti-inflammatory cytokines was the lowest.